2013
DOI: 10.1517/13543784.2013.836488
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacotherapeutics for substance-use disorders: a focus on dopaminergic medications

Abstract: Introduction Illicit substance-use is a substantial public health concern, contributing over $150 billion in costs annually to Americans. A complex disease, a substance-use disorder affects neural circuits involved in reinforcement, motivation, learning and memory, and inhibitory control. Areas covered The modulatory influence of dopamine in mesocorticolimbic circuits contributes to encoding the primary reinforcing effects of substances and numerous studies suggest that aberrant signaling within these circui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 147 publications
(172 reference statements)
0
33
0
Order By: Relevance
“…Cocaine is a potent inhibitor of monoamine transporters, including DA, serotonin, and NE transporters (Fleckenstein et al 2000; Miller et al 2001). Cocaine binds at the DA transporter and inhibits neurotransmitter reuptake, leading to a build-up of extracellular DA levels and potentiation of mesolimbocortical pathways (Haile et al 2012b; Verrico et al 2013). The distribution half-life of cocaine from an IV dose is about 10 min and the elimination T-½ of cocaine is ~1 hour (50–80 min).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cocaine is a potent inhibitor of monoamine transporters, including DA, serotonin, and NE transporters (Fleckenstein et al 2000; Miller et al 2001). Cocaine binds at the DA transporter and inhibits neurotransmitter reuptake, leading to a build-up of extracellular DA levels and potentiation of mesolimbocortical pathways (Haile et al 2012b; Verrico et al 2013). The distribution half-life of cocaine from an IV dose is about 10 min and the elimination T-½ of cocaine is ~1 hour (50–80 min).…”
Section: Methodsmentioning
confidence: 99%
“…A variety of neuropharmacological strategies and targets are being pursued as treatments for cocaine addiction. Some of these strategies include blocking cocaine’s positive subjective effects, reducing cocaine craving, treating underlying co-morbid conditions that may predispose individuals to developing dependence, and stress reduction to prevent relapse (Haile & Kosten 2013; Haile et al 2012b; Verrico et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies also confirmed how pharmacotherapy might be beneficial in DUDs treatment (for overviews see: [13][14][15]). Furthermore, a variety of psychological and behavioral therapies also demonstrated to be effective (e.g., cognitive-behavioral therapy [CBT], motivational enhancement therapy, 12-step facilitation therapy [16][17][18][19]).…”
Section: Doi: 101159/000490762mentioning
confidence: 95%
“…As many of the subjective and reinforcing effects of cocaine have traditionally been attributed to dopaminergic deficiencies within the mesocorticolimbic pathways (Koob, 2003; Volkow, Fowler, Wang, & Goldstein, 2002), potentiating dopamine transmission via “agonist therapy” has provided an important therapeutic target for reducing withdrawal symptoms and preventing relapse (Verrico, Haile, Newton, Kosten, & De La Garza, 2013). However, many of these candidate medications have been limited due to their high abuse liability and high prevalence of side effects (Diana, 2011; Thanos et al, 2004).…”
Section: Other Potential Anxiolytics and Cognitive Enhancersmentioning
confidence: 99%